Mechanisms of human rights protection in Colombia from pedagogy - Cifuentes-Medina, José Eriberto; Higuera-Sandoval, Jairo Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2014)
We aim to share an educational experience the mechanisms of protection of human rights in Colombia, developed in the subjects of Political Culture and Ethics with the students of Regency of Pharmacy, in order to strong knowledge about the Constitution of Colombia, institutions and legal forms of protection.  The proposed pedagogical reflection was implemented in three phases: the firs occurred  on the theoretical foundation of human rights and «mechanisms of protection», from  different perspectives; in the second one some apprehension of strategies of the following  mechanisms were designed: right to petition, action of protection, habeas corpus, habeas data, popular action and group action and of the institutions: Office of the Solicitor,  and Ombudsman Office, according to the 1991 Constitution, and the third phase corresponds to developing scenarios and activities of the thematic educational thinking,  in order to strong the education of students, to highlight the value of justice and equality, so that the exercise of mechanisms to protect, at least the fundamental rights, is not utopian, especially when it comes to people working in the health sector. The results have been valuable for teaching exercise on grounds of human rights instructional management mechanisms like 1991 Constitution. In terms of the learning process of students, it was envisioned achievements in writing, appropriation and  management of legal forms. From this proposal they are able to deal with the defense of human rights, the theoretical found action, because they are open to knowledge and reflection, capable of making utopias in possible avenues of witness and memory exercise.